Molecular allergology and its application in prevention, diagnosis and therapy - Podzhilkova, Aleksandra; Nagl, Christoph; Hoffmann-Sommergruber, Karin (Frontiers in Allergy, 2023)
Allergic diseases represent a relevant global health problem, affecting adults and children and pose a significant burden for health care systems. In addition, the disease is still under-recognized and harmonized diagnostic tools and management plans for the patients are still lacking. In this review the most important aspects of the diagnosis of allergic diseases are summarized and the contribution of Molecular allergology to this area is highlighted.